Analysis of Digital Influencer Advertising Content on the @lozyhijab account as a Marketing Communication Strategy for Muslim Clothing on Instagram Accounts - Anggrayni, Dewi; Suharti, Titing; Nurwahyuni, Risa Putri; Melyanti, Melyanti (prodima@fe.uika-bogor.ac.id, 2025)
This study aims to analyze the marketing strategy of @lozyhijab communication carried out through influencer promotional content on Instagram during August-September 2024. In today's digital era, influencer marketing is one of the effective methods in reaching a wider audience, especially in the Muslim clothing segment. The research uses a descriptive qualitative approach with a focus on three main indicators: branding, engagement, and content visibility. Of the 2 influencers involved, influencers Alyah Balqis and Hamidah Rachmayanti showed significant contributions to this campaign. Alyah Balqis promotes elegant Muslim women's casual clothing, while Hamidah Rachmayanti focuses on sharia clothing for worship. Alyah's content highlights modern design through dynamic visuals that increase brand visibility, while Hamidah's content reinforces religious values with an authentic approach that are relevant to his audience. In addition, active interactions in the comment column, such as Alyah's friendly responses and Hamidah's personal communication, improve emotional relationships with customers, strengthen loyalty, and increase trust in the brand. The study concludes that choosing the right influencers with a tailored communication strategy on each indicator can have a positive impact in today's era of online marketing if they are responsible for choosing the right influencers and using the right methods to get their message across.